Collaboration and knowledge generation in an 18-year quality improvement research programme in Australian Indigenous primary healthcare: a coauthorship network analysis. Issue 5 (6th May 2021) - Bailie, Jodie; Potts, Boyd Alexander; Laycock, Alison Frances; Abimbola, Seye; Bailie, Ross Stewart; Cunningham, Frances Clare; Matthews, Veronica; Bainbridge, Roxanne Gwendalyn; Conte, Kathleen Parker; Passey, Megan Elizabeth; Peiris, David
Abstract : Objectives: Though multidisciplinary research networks support the practice and effectiveness of continuous quality improvement (CQI) programmes, their characteristics and development are poorly understood. In this study, we examine publication outputs from a research network in Australian Indigenous primary healthcare (PHC) to assess to what extent the research network changed over time. Setting: Australian CQI research network in Indigenous PHC from 2002 to 2019. Participants: Authors from peer-reviewed journal articles and books published by the network. Design: Coauthor networks across four phases of the network (2002–2004; 2005–2009; 2010–2014; 2015–2019) were constructed based on author affiliations and examined using social network analysis methods. Descriptive characteristics included organisation types, Indigenous representation, gender, student authorship and thematic research trends. Results: We identified 128 publications written by 308 individual authors from 79 different organisations. Publications increased in number and diversity over each funding phase. During the final phase, publication outputs accelerated for organisations, students, project officers, Indigenous and female authors. Over time there was also a shift in research themes to encompass new clinical areas and social, environmental or behavioural determinants of health. Average degree (8.1), clustering (0.81) and diameter (3) indicated a well-connected network, with a core-periphery structure in each phase (p≤0.03) rather than a single central organisation (degree centralisation=0.55–0.65). Academic organisations dominated the core structure in all funding phases. Conclusion: Collaboration in publications increased with network consolidation and expansion. Increased productivity was associated with increased authorship diversity and a decentralised network, suggesting these may be important factors in enhancing research impact and advancing the knowledge and practice of CQI in PHC. Publication diversity and growth occurred mainly in the fourth phase, suggesting long-term relationship building among diverse partners is required to facilitate participatory research in CQI. Despite improvements, further work is needed to address inequities in female authorship and Indigenous authorship.